MODERN ASPECTS OF BUILDING THE GENERAL PHYSICAL TRAINING OF FEMALE ATHLETES IN THE COSSACK FIGHT, TAKING INTO ACCOUNT THE PHASES OF THE OVARIAN-MENSTRUAL CYCLE - Lytvynenko, A. M.; Mulyk, V. V. (Rehabilitation and Recreation, 2024)
The relevance of the research problem is due to the fact that at the current stage of the development of Ukrainian national martial arts, their popularity among women of various age groups is growing and there is a pronounced tendency to increase the number of female participants in sports competitions. Purpose is to determine the change in indicators of general physical fitness during the preparatory period of female athletes of the Ukrainian national martial art – Cossack Fight, under the influence of the variability of training loads in different phases of the ovarian-menstrual cycle. Material and methods. 20 qualified sportswomen participated in the study, who were divided into two groups – control (n=10) (1 – MSU; 2 – KMSU; 7 – 1 sports category) and experimental (n=10) (1 – MSU; 2 – KMSU ; 7 – 1 sports category). The age of female athletes who took part in the study was 17–24 years. The following research methods were used: theoretical analysis and generalization of data from special literature, methods of pedagogical control (testing, pedagogical observations, methods of mathematical statistics). The results. During the general preparatory stage of the preparatory period of the annual training, indicators of the general physical fitness of the control group improved. The overall group indicators in bending and extension of the arms in the supine position increased significantly by 1.3 times (t=2.24; p<0.05), hanging on bent arms on the crossbar by 1.4 s. (t=2.15; p<0.05) and running 2000 m in 28.5 seconds. (t=2.31; p<0.05). Significantly better average group results during the general preparatory stage of the preparatory period, which took into account physical loads in separate phases of the ovarian-menstrual cycle of women (significant and large loads were used only in the post-menstrual and post-ovulatory phases) were obtained on most indicators. Thus, the indicators in bending and extension of the arms in the supine position are significantly higher by 2.5 times (t=2.54; p<0.05), while standing on bent arms at the crossbar by 2.3 s (t=2.46; p<0.05). р<0.05), long jump from a standing position by 9.9 cm (t=3.26; р<0.01), transition from a squat position to a lying position in 1 min. for 3.4 times (t=3.82; p<0.01), shuttle running 4 x 9 m for 0.6 s (t=2.56; p<0.05), jumping with a rope from the leg for leg in 1 min. by 13.1 times (t=4.55; p<0.001), forward body tilts while standing on the gymnastic bench by 0.6 cm (t=2.37; p<0.05), trunk lifts from the starting position supine position by 3.5 cm (t=2.85; p<0.05). After carrying out the training process according to the indicated methods, more significant results were obtained by the athletes of the experimental group in the long jump from a place with two legs (t=2.99; p<0.05), shuttle running (t=2.26; p<0.05), jumping rope from foot to foot in 1 min. (t=2.95; p<0.05). Conclusions. The application in the training process of general physical training of significant and heavy loads in the post-menstrual and post-ovulatory phases of a ovarian-menstrual cycle and reducing the load in other phases contributes to the reliable growth of indicators of physical fitness of female athletes. Taking into account the ovarian-menstrual cycle in the experimental group when planning the training process of women from general physical training in the Ukrainian national form of martial arts – the Cossack Fight, led to a greater increase in the indicators of general physical fitness of female athletes than in the control group, which trained according to the standard method.